2016
DOI: 10.1075/tis.11.2.04ple
|View full text |Cite
|
Sign up to set email alerts
|

The effect of informational load on disfluencies in interpreting

Abstract: This article attempts to measure the cognitive or informational load in interpreting by modelling the occurrence rate of the speech disfluency uh(m). In a corpus of 107 interpreted and 240 non-interpreted texts, informational load is operationalized in terms of four measures: delivery rate, lexical density, percentage of numerals, and average sentence length. The occurrence rate of the indicated speech disfluency was modelled using a rate model. Interpreted texts are analyzed based on the interpreter's output … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 29 publications
2
27
0
1
Order By: Relevance
“…However, delivery rate was significant only for the source texts, whereas lexical density was significant only in the comparison between the interpreted (target) texts and the monolingual texts. The results reported by Plevoets and Defrancq (2016) thus clearly reflect cognitive load, but they also underline the need to differentiate between the cognitive demands of comprehension or listening and those of language production (which we will call 'input load' and 'output load' , respectively). Corpus-based research is still sporadic in interpreting studies, despite Shlesinger's (1998) plea for its more widespread adoption.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, delivery rate was significant only for the source texts, whereas lexical density was significant only in the comparison between the interpreted (target) texts and the monolingual texts. The results reported by Plevoets and Defrancq (2016) thus clearly reflect cognitive load, but they also underline the need to differentiate between the cognitive demands of comprehension or listening and those of language production (which we will call 'input load' and 'output load' , respectively). Corpus-based research is still sporadic in interpreting studies, despite Shlesinger's (1998) plea for its more widespread adoption.…”
Section: Introductionmentioning
confidence: 99%
“…A crucial aspect of our analysis is that we will study the four informational load indicators identified above (delivery rate, lexical density, proportion of num-bers and formulaicity) in both the source text and its simultaneous interpretation (following Plevoets & Defrancq 2016). The reason is that the interpreter's cognitive load is expected to increase not only when informational load is higher in the source text, but also when the interpretation is faster and/or lexically/numerically denser.…”
Section: Cognitive Load: Definition and Measuresmentioning
confidence: 99%
See 3 more Smart Citations